Mitochondrial transport mediates survival of retinal ganglion cells in affected LHON patients. (10th April 2020) - Yang, Tien-Chun; Yarmishyn, Aliaksandr A; Yang, Yi-Ping; Lu, Pin-Chen; Chou, Shih-Jie; Wang, Mong-Lien; Lin, Tai-Chi; Hwang, De-Kuang; Chou, Yu-Bai; Chen, Shih-Jen; Yu, Wei-Kuang; Wang, An-Guor; et al.
Abstract: The mutations in the genes encoding the subunits of complex I of the mitochondrial electron transport chain are the most common cause of Leber's hereditary optic neuropathy (LHON), a maternal hereditary disease characterized by retinal ganglion cell (RGC) degeneration. The characteristics of incomplete penetrance indicate that nuclear genetic and environmental factors also determine phenotypic expression of LHON. Therefore, further understanding of the role of mutant mitochondrial nicotinamide adenine dinucleotide dehydrogenase subunit proteins and nuclear genetic factors/environmental effects in the etiology of LHON is needed. In this study, we generated human-induced pluripotent stem cells (hiPSCs) from healthy control, unaffected LHON mutation carrier, and affected LHON patient. hiPSC-derived RGCs were used to study the differences between affected and unaffected carriers of mitochondrial DNA point mutation m.11778G > A in the MT-ND4 gene. We found that both mutated cell lines were characterized by increase in reactive oxygen species production, however, only affected cell line had increased levels of apoptotic cells. We found a significant increase in retrograde mitochondria and a decrease in stationary mitochondria in the affected RGC axons. In addition, the messenger RNA and protein levels of KIF5A in the LHON-affected RGCs were significantly reduced. Antioxidant N-acetyl-L-cysteine could restore the expression of KIF5A and the normal pattern of mitochondrial movement in the affected RGCs. To conclude, we found essential differences in the mutually dependent processes of oxidative stress, mitochondrial transport and apoptosis between two LHON-specific mutation carrier RGC cell lines, asymptomatic carrier and disease-affected, and identified KIF5A as a central modulator of these differences.